Who is Educating EFL Teachers : a Qualitative Study of in-service in Colombia (2003)
ABSTRACT: This paper reports the findings of a qualitative study designed to explore the professional needs of EFL teachers. Data collection techniques included focus groups, a questionnaire, and in-depth interviews. The results suggest that many EFL teachers may not experience the benefits of the professional options provided by institutions of higher education; less formal and structured training opportunities, such as professional conferences and publishers’ sessions, are considered by many of them as the real agents of their education. The implications of these beliefs for the professionalization of the teachers are discussed.